2016
DOI: 10.1021/acs.jchemed.5b00618
|View full text |Cite
|
Sign up to set email alerts
|

Tournament of Young Chemists in Ukraine: Engaging Students in Chemistry through a Role-Playing Game-Style Competition

Abstract: With more than 20 years of history, the Tournament of Young Chemists is an innovative, cross-disciplinary competition that promulgates the everyday life of scientists into the classrooms and on the contest stage. Original, open-type problems, unrestricted access to scientific data sources, and personal interaction with researchers from different fields of chemistry aim to develop a broad range of skills that prepare the participants for their future academic endeavors such as thinking, communication, reasoning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…After a few words to introduce the rules, the teacher reveals the first two teams who will compete against each other on the model of a hip-hop battle or an oratorical joust . The two teams are chosen by drawing lots.…”
Section: Description Of the Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…After a few words to introduce the rules, the teacher reveals the first two teams who will compete against each other on the model of a hip-hop battle or an oratorical joust . The two teams are chosen by drawing lots.…”
Section: Description Of the Activitymentioning
confidence: 99%
“…After a few words to introduce the rules, the teacher reveals the first two teams who will compete against each other on the model of a hip-hop battle 50 or an oratorical joust. 51 The two teams are chosen by drawing lots. From this point, students are expected to be able to present a question, a topic, or a theme on the chosen chemical process.…”
Section: The Battlementioning
confidence: 99%
“…Therefore, cooperative learning tends to result in having some bystanders (Radinsky, 2008) or free-riders (Cera Guy et al, 2019; Topping et al, 2011; Zambrano et al, 2019) who do not participate in learning activities, as the authors observed in the classrooms. In addition to these factors, with conditions like role division (de Beer and Petersen, 2017; Johnson, 2009; Law, 2014; Svechkarev and Grygorovych, 2016) and rewards (Johnson, 2009; Sears and Pai, 2012; Slavin, 2015; Unrau et al, 2015) it would become harder for those with questions to seek for help. This is because efficiency to come up with the answers towards the tasks is prioritised in the process of cooperative learning described above.…”
Section: Meaning Of Teachers’ Academic Experiences: Expertisementioning
confidence: 99%
“…There are two representative approaches to group learning, cooperative learning being the more favoured one that many practitioners and researchers are engaged with (Van Ryzin and Roseth, 2018). Cooperative learning aims to let students achieve academic and social goals based on role division (Johnson, 2009; Law, 2014; Svechkarev and Grygorovych, 2016) or accountability towards individually assigned tasks (de Beer and Petersen, 2017), rewards (Johnson, 2009; Sears and Pai, 2012; Slavin, 2015; Unrau et al, 2015) and sometimes competition between groups (Slavin, 2015; Svechkarev and Grygorovych, 2016; Williams and Sheridan, 2010). In many South East Asian countries, where the authors have been collaborating with teachers, cooperative learning has been introduced, such as in Indonesia (Harjanto et al, 2017; Khong et al, 2017), Singapore (Jacobs and Renandya, 2019; Koh et al, 2007), Thailand (Kijkuakul, 2019) and Vietnam (Nguyen-Phuong-Mai, 2018; Nguyen-Phuong-Mai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating competitions into chemistry education is another well-studied method for increasing both classroom engagement and morale. Furthermore, competitions are successful in the context of organic chemistry theory and nomenclature. Given the advantages of classroom competitions and the recent development of chemistry-themed serious educational games, ,,, implementing a class competition that teaches organic chemistry skills is a promising avenue toward improving the wellness and chemistry knowledge of social-distancing, distance-learning, organic chemistry students.…”
Section: Introductionmentioning
confidence: 99%